Evolution of Academic Literature on Tax Regulation: A Bibliometric Approach 2015-2025 - Sopriyanti, Mita; Santoso, Rachmat Agus; Fitriana, Fitriana (Penerbit Goodwood, 2025)
Purpose: This research aims to trace the development of literature related to tax regulations in various countries including articles published from 2015 to 2025 using bibliometric methods based on the analysis of Co-occurrence units All keywords, Bibliographic coupling unit country and documents. Methodology/approach: Bibliometric analysis methodology was conducted on 191 articles between 1976 and 2025. Data was obtained from Scopus meta data which was then analyzed using Vosviewer. Results/findings: In conclusion, the topic of